(untitled) (Comprehensive Journal of Science, 2026)
Like all fields of human creativity, the visual arts have witnessed significant developments in styles and forms of expression, recorded under the names of schools, with realism at the forefront. Realism, by virtue of its long history, represents an artistic experiment undertaken by creators in imitating nature and reality without any intervention, resembling photography. The train of artistic development has continued to present the scene with images of schools with diverse concepts and visions. In recent years, visual art has ceased to focus on art that embodies established schools and styles. True visual art is a creative process and a message it carries to its society. The modernist movement in the visual arts has witnessed intellectual and aesthetic transformations in all aspects of life, becoming one of the most important turning points in the history of art. No art form or style has been immune to this transformation, as change and transformation have become the hallmark of the modern age. These formal and stylistic transformations in art were not born of a fixed moment or a specific artistic and aesthetic decision. Modernization in art is based on actual modernization within a constantly evolving movement. Modern art, which was born with global evolutionary thought in all aspects of human knowledge and its origins, has given science, philosophy, literature, education, and culture. This began with the Impressionist movement and its revolution against the traditions of art practice in Europe, whose beginnings date back to Plato and continued for more than three thousand years. This was when Plato launched his famous materialist theory of fine arts, within the framework of the philosophy of truth, goodness, and beauty, and described it as a reformulation of the surrounding visuals in works characterized by imitation and mimicry. This gave modern art the keys to expression through continuous experimentation in thought and application, and there became distinctive artistic signs, which included all kinds of plastic art through the fragmentation of form and its reformulation in space. This prompted artists to search for those basic laws in the system of building the artwork they create, while dissolving the boundaries between the classifications of arts that were advocated by Greek civilization and continued until the beginning of the twentieth century. Thus, diverse plastic forms emerged, where the term plastic art became the main axis of artistic expression for the producing artist.